Adsorption of organic compounds at the surface of Enceladus' ice grains. A grand canonical Monte Carlo simulation study. Issue 1 (2nd January 2022) - Joliat, Julien; Patt, Antoine; Simon, Jean Marc; Picaud, Sylvain
ABSTRACT: In this paper, we characterise the adsorption of ethylene, propanol and hexanal molecules on crystalline ice by grand canonical Monte Carlo simulations performed at 236 K, a temperature which is typical of some Enceladus' environments. We show that at low coverage of the ice surface, the adsorption of propanol and hexanal is driven by the interaction of these molecules with the ice phase and, as a consequence, the adsorbed molecules lie more or less parallel to the ice surface. On the other hand, upon saturation, the adsorbate–adsorbate interactions become more and more important and the molecules tend to become tilted with respect to the surface, the aliphatic chain pointing towards the gas phase, while the polar head of propanol and hexanal molecules always stays attached to the ice surface, irrespective of the coverage. By contrast, the ethylene molecules do not show any strong affinity for the ice surface because of the corresponding weak binding energy. These results are in good agreement with the major features provided by the available experiments on similar systems.